UMP receives RM1.085 million - UMP, PNC
UMP Holdings Sdn. Bhd. (UMPH), a subsidiary of Universiti Malaysia Pahang (UMP) and Centre of Continuing Education and Professional Development (CENFED) contributed RM1 million and RM85,689.53, respectively to the university.